Study the Effect of Thickness on the Electrical Conductivity and Optical Constant of Co3O4 Thin Films - Al-Maiyaly, Bushra K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research the Cobalt Oxide (Co3O4) films are prepared by the method of chemical spray pyrolysis deposition at different thicknesses such that (250, 350, 450, and 550) Â± 20 nm.      The optical measurement shows that the Co3O4 films have a direct energy gap, and they in general increase with the increase of the thickness. The optical constants are investigated and calculated such as absorption coefficient, refractive index, extinction coefficient and the dielectric constants for the wavelengths in the range (300-900) nm.     The electrical conductivity (Ïƒ) and the activation energies (Ea1, Ea2) have been investigated on (Co3O4) thin films as a function of thickness. The films contain two types of transport mechanisms, and the electrical conductivity (Ïƒ) increases whereas the activation energy (Ea) would decrease as the films thickness increases.